Clay contemporary ceramic artisans - Bell, Amber Creswell (Thames & Hudson Australia, 2016)
"Ceramics is back in a big way, experiencing a steady surge of interest and popularity not seen since the 1970s. The return to the handmade has been driven by our increasingly digital lives and there are now more makers, sellers and collectors than ever. There is also a new desire for unique objects made by hand and the imperfections associated with the marks of the maker. Pottery captures this authenticity in ways no other medium can. From decorative pieces to the primarily functional to sculptural works pushing the boundaries of the medium, Clay surveys the richly creative output of over 50 studio potters from around the world. It is a celebration of a new generation of artisans working in clay, a snapshot not necessarily of what is happening at elite gallery level, but rather a behind-the-scenes look at the unique and eclectic offerings from small studios around the world." -- Publisher's website